The role of bond covenants and short-term debt: evidence from Brazil - Silva, Vinicius Augusto Brunassi (2011)
This paper examines the relationship between covenants, short-term and long-term debt with companies which face growth opportunities. Using a sample of 159 Brazilian corporate bonds, we found evidence that: 1) Covenants and short-term debt are substitute tools to minimize agency conflict, since they presented a negative and significant relation and; 2) The negative relation between short-term debt and growth opportunities might be attenuated in the presence of covenants.